The Influence of Parental Prosocial Behavior on Children's Participation in Volunteer Activities - Wahyudhia Zalpa MZ (Da'wa Faculty of Islamic State University Salatiga, 2024)
Modern society is assumed to be pragmatic, selfish, and individualistic. However, this assumption seems to be refuted by the results of several surveys conducted in Indonesia, which show a trend of increasing prosocial behavior and volunteerism in society. It is interesting to study prosocial behavior in society, especially among students, because students are bound by the tri dharma of higher education, which includes the principles of community service. This research does not deny the role of socialization in individual behavior. Therefore, this study aims to examine the influence of parents' prosocial behavior as the primary socialization agent on the participation of child (student) volunteers. This research uses a correlation study method with the moderating variables socialization and children's prosocial behavior, which are then tested as the dependent variable with socialization as the moderating variable. The population in this study were all university students in East Java. The sample in this study was taken using a purposive sampling technique. The study sample consisted of 100 people, with details of 50 from Surabaya and 50 from Sidoarjo. This research uses several SPSS tests such as Pearson correlation, MRA regression test, t-test, and others. This study's results indicate a small influence between parents' prosocial behavior and child volunteer participation. The moderating variables of children's socialization and prosocial behavior have strengthened the influence between variables.